2002
DOI: 10.1097/00001756-200207020-00016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resting activity of the oral somatosensory cortex in obese subjects

Abstract: The cerebral mechanisms underlying excess food intake in obese subjects are poorly understood. We used PET and 2-deoxy-2[18F]fluoro-D-glucose to assess differences in regional brain metabolism between obese and lean subjects at rest. Brain metabolic images were analyzed using statistical parameter maps. We found that obese subjects have significantly higher metabolic activity in the bilateral parietal somatosensory cortex in the regions where sensation to the mouth, lips and tongue are located. The enhanced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 20 publications
10
79
0
Order By: Relevance
“…The latter observation corresponded to regions where a previous study had revealed enhanced activity in obese subject tested at baseline (non stimulation) (Wang et al 2002) (Fig.7 d,e). An enhanced activity of regions that process palatability could make obese subjects favor food over other natural reinforcers, whereas decreased activation of dopaminergic targets by the actual food consumption might lead to overconsumption as a means to compensate for weak D2R-mediated signaling (Stice et al 2008a).…”
Section: The Impact Of Dysfunction In Inhibitory Controlsupporting
confidence: 85%
“…The latter observation corresponded to regions where a previous study had revealed enhanced activity in obese subject tested at baseline (non stimulation) (Wang et al 2002) (Fig.7 d,e). An enhanced activity of regions that process palatability could make obese subjects favor food over other natural reinforcers, whereas decreased activation of dopaminergic targets by the actual food consumption might lead to overconsumption as a means to compensate for weak D2R-mediated signaling (Stice et al 2008a).…”
Section: The Impact Of Dysfunction In Inhibitory Controlsupporting
confidence: 85%
“…Though there is limited literature on the role of the somatosensory cortex in food intake and obesity. Imaging studies reported activation of the somatosensory cortex in normal weight subjects with exposure to visual images of low caloric foods (Killgore et al, 2003) and with satiety (Tataranni et al, 1999), and we had shown higher than normal baseline metabolism in the somatosensory cortex in obese subjects (Wang et al, 2002). Also a recent study reported that in obese individuals with leptin deficiency administration of leptin normalized their body weight and reduced brain activation in parietal cortex while viewing food-related stimuli (Baicy et al, 2007).…”
Section: Correlation Between D2r and Somatosensory Cortexsupporting
confidence: 58%
“…This led us to reconsider the possibility that the higher risk for overeating in subjects with low D2 receptor availability may also be driven by DA's regulation of DLPFC and medial prefrontal regions, which have been shown to participate in the inhibition of inappropriate behavioral response tendencies (Mesulam, 1985;Le Doux, 1987;Goldstein and Volkow, 2002). Thus we performed secondary analysis on data from subjects that had been previously recruited as part of studies to evaluate changes in D2 receptors (Wang et al, 2001) and of brain glucose metabolism in obesity (Wang et al, 2002) and data from age matched controls. Our working hypothesis was that D2 receptor availability in obese subjects would be associated with disrupted activity in prefrontal regions.…”
mentioning
confidence: 99%
“…6 A baseline comparison of regional brain glucose metabolism between obese (Ob) and normal weight subjects revealed that even without FS, Ob subjects had significantly higher metabolism in the parietal somatosensory cortex where the lips and tongue are represented, which was interpreted to reflect increased sensitivity of the regions that process food palatability. 7 Studies in laboratory animals have also identified regional activation of the prefrontal cortex, 8 amygdala 9 and nucleus accumbens 10 upon exposure to rewarding food stimuli. Here, we evaluate the regional brain metabolic responses to a food stimulus to assess the brain response to food reinforcers.…”
Section: Introductionmentioning
confidence: 99%